The Declaration of environmental damage in administrative proceedings: Is it an effective means to fully repair environmental damage Per Se? - Delgado-Garrido, Andrés (DICERE Revista de Derecho y Estudios Internacionales, 2025)
The Constitution of the Republic of Ecuador marked a global milestone in the protection of nature. For the first time worldwide, nature was granted the status of a subject with rights. As such, it became necessary to implement several measures to ensure the respect of natural life cycles and prevent anthropogenic activities from resulting in environmental damage. Nevertheless, it is undeniable that the execution of activities, projects, or developments inherently carries a certain degree of risk for society. Although mechanisms exist to prevent environmental harm, damage may still occur. The Constitution is clear in this regard, obligating the State to directly address and remedy environmental damage when it occurs, and subsequently initiate administrative and judicial actions against the operator responsible for causing said damage. The declaration of environmental damage can be carried out through two avenues: (i) administrative; and (ii) judicial. This article aims to analyze whether declaring environmental damage through administrative proceedings constitutes an effective mechanism in fulfilling the State’s obligation of providing full reparation. To achieve this, it is necessary to examine the various aspects of environmental damage and the procedures established under the Organic Environmental Code, the Organic Administrative Code, and the Regulations of the Organic Environmental Code, in order to determine environmental damage and understand the implications this has for both the operator and the State.